A Qualitative Study on The Challenges Faced by English Teachers In Applying Differentiated Instruction - Sri Supiah Cahyati (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dwijendra, 2026)
This study explores the challenges faced by English teachers in implementing differentiated instruction (DI) within the context of senior high schools in Indonesia. Recognizing the increasing diversity in student abilities, interests, and learning styles, differentiated instruction has emerged as a student-centered approach aimed at addressing these differences. Despite its theoretical strengths, practical implementation remains complex. Employing a qualitative descriptive method, this research gathered data through in-depth interviews, classroom observations, and document analysis involving English teachers with at least two years of teaching experience. The findings reveal five major challenges: (1) difficulties in adjusting content, teaching methods, and assessments; (2) time constraints and high workload; (3) limited facilities and instructional resources; (4) internal barriers such as limited knowledge and low teacher confidence; and (5) adaptive strategies developed by teachers. Despite significant constraints, teachers demonstrated resilience by employing flexible grouping, task modifications, reflective practices, and peer collaboration. The study concludes that successful DI implementation requires more than individual teacher initiative—it demands systemic support, adequate training, and enabling school environments. These insights can inform educational policy, curriculum development, and teacher training programs to promote more inclusive and effective English language instruction.